2023
DOI: 10.21037/jtd-22-1685
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of immunoradiotherapy for advanced non-small cell lung cancer: a retrospective comparative cohort study

Abstract: Background Treatment of radiotherapy (RT) combined with immune checkpoint inhibitor (ICI) may remarkably improve the prognosis in patients with metastatic non-small cell lung cancer (NSCLC). However, the treatment time of RT, irradiated lesion and the optimum combined scheme, have not been fully determined. Methods Data regarding overall survival (OS), progression-free survival (PFS), treatment response, and adverse events of 357 patients with advanced NSCLC treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…44 This mechanism might explain the significant clinical benefit achieved with the platinum-pemetrexed and pembrolizumab combination even in the subgroup of metastatic NSCLC patients with PD-L1 negative tumors, 45 and the higher objective response rate and disease control rate in patients receiving radiotherapy and immunotherapy in comparison to immune-monotherapy. 45,46 Contradictory to this hypothesis, some clinical trials described a downregulation of the PD-L1 expression on tumor cells after a cisplatin-gemcitabine combination, paclitaxel-based regimen, or TKIbased therapy. 47,48 The primary limitation of our study lies in its retrospective single-center design and the relatively limited number of included patients.…”
Section: Discussionmentioning
confidence: 99%
“…44 This mechanism might explain the significant clinical benefit achieved with the platinum-pemetrexed and pembrolizumab combination even in the subgroup of metastatic NSCLC patients with PD-L1 negative tumors, 45 and the higher objective response rate and disease control rate in patients receiving radiotherapy and immunotherapy in comparison to immune-monotherapy. 45,46 Contradictory to this hypothesis, some clinical trials described a downregulation of the PD-L1 expression on tumor cells after a cisplatin-gemcitabine combination, paclitaxel-based regimen, or TKIbased therapy. 47,48 The primary limitation of our study lies in its retrospective single-center design and the relatively limited number of included patients.…”
Section: Discussionmentioning
confidence: 99%
“…The study ndings demonstrated that the combination of ICIs and radiation therapy resulted in improved long-term outcomes and tumor remission in patients with advanced NSCLC. In the study, out of the total 202 cases, 160 cases (79.2%) underwent radiotherapy prior to receiving immunotherapy, while 42 cases (20.8%) received concurrent radiotherapy and immunotherapy [25]. There is a lack of research examining the e cacy of advanced NSCLC immunotherapy followed by thoracic radiotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In Gao's study, the incidence of pneumonitis was found to be signi cantly different between the two groups (P = 0.007). The immunotherapy combined with radiotherapy group had 36 cases (17.8%), while the immunotherapy alone group had 12 cases (7.7%) [25]. A retrospective analysis was conducted on patients who had previously encountered side effects related to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%